2017
DOI: 10.3389/fmars.2017.00052
|View full text |Cite
|
Sign up to set email alerts
|

Resource Competition Affects Plankton Community Structure; Evidence from Trait-Based Modeling

Abstract: Understanding the phenology of phytoplankton species is a challenge and despite a lot of theoretical work on competition for resources, this process is under-represented in deterministic models. To study the main driver of the species selection, we used a trait-based model that keeps phenotypic variability through physiological trait parameterization. Next, we validated the results by using the toxic dinoflagellate Alexandrium minutum which is a toxic species. Due to their monitoring, we show that harmful alga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 69 publications
(85 reference statements)
1
14
1
Order By: Relevance
“…Competition can manifest either indirectly through intrinsic physiological and biochemical adaptation, with the fittest species outcompeting the others (Krebs, 2001;Morin, 2009), or directly through allelopathy, mainly with species that produce chemical inhibitors (Rice, 2012). Models revealed that competition is an important factor that regulates planktonic community structure during blooms (Huisman et al, 1999;Hashioka et al, 2013;Sourisseau et al, 2017). Furthermore, field and laboratory studies identified competition among phytoplankton species during bloom (Sakshaug and Olsen, 1986;Sommer, 1988).…”
Section: Network Complexity Increases During Phytoplankton Bloommentioning
confidence: 99%
“…Competition can manifest either indirectly through intrinsic physiological and biochemical adaptation, with the fittest species outcompeting the others (Krebs, 2001;Morin, 2009), or directly through allelopathy, mainly with species that produce chemical inhibitors (Rice, 2012). Models revealed that competition is an important factor that regulates planktonic community structure during blooms (Huisman et al, 1999;Hashioka et al, 2013;Sourisseau et al, 2017). Furthermore, field and laboratory studies identified competition among phytoplankton species during bloom (Sakshaug and Olsen, 1986;Sommer, 1988).…”
Section: Network Complexity Increases During Phytoplankton Bloommentioning
confidence: 99%
“…are defended mixotrophs and a group of organisms known to form toxic algal blooms (TAB; Burkholder et al 2008). Such blooms are usually observed under summer conditions of nutrient limitation and concurrent with the stabilization of the water column (Hakanen et al 2012, Gettings et al 2014, Sourisseau et al 2017) and the highest seasonal abundance of copepod grazers (Kiørboe and Nielsen 1994). These are the conditions that stimulate the induction of costly defense in dinoflagellates (Chakraborty et al 2018).…”
Section: The Relation Between Defense and Trophic Strategiesmentioning
confidence: 99%
“…The availability of macronutrients and micronutrients play a key role in structuring the phytoplankton community (Vyverman et al 2007). Nutrient requirements within the phytoplankton community are highly variable, leading to interspecific competition for nutrient resources (Sourisseau et al 2017). As different phytoplankton groups have distinct nutrient requirements and means of nutrient acquisition, the addition of a nutrient can cause differential responses in different segments of the phytoplankton community.…”
Section: Introductionmentioning
confidence: 99%